Novel surgical options for gastroesophageal reflux disease. (July 2015) - Chiu, Jenny; Soffer, Edy
<x xml:space="preserve">Abstract</x> There are limited options to patients with gastroesophageal reflux disease (GERD) who are not satisfied with acid suppression therapy. Fundoplication, the standard surgical procedure for GERD, is effective but is associated with adverse side effects and has thus been performed less frequently, creating a need for alternative surgical interventions that are effective, yet less invasive and reversible. Lately, two such interventions were developed: the magnetic sphincter augmentation and electrical stimulation of the lower esophageal sphincter. Human studies describing safety and efficacy over a follow-up period of a number of years have been published, documenting efficacy and safety of these interventions. Future studies should clarify the role of these procedures in the spectrum of GERD therapy.